Development of a Sexually Transmitted Disease Client-friendly Unit at a Primary Care Clinic in Malaysia: Lessons Learnt - Pannir Selvam, Sheela Bai; Khoo, Ee Ming; Chow, Suet Yin; Wong, Ping Foo; Mohsin, Siti Shafiatun; Abdullah, Adina; Choo, Wan Yuen (Lippincott, Williams & Wilkins, 2019)
Management of sexually transmitted diseases and human immunodeficiency virus is challenging due to the social stigma attached. We describe the development of a client-friendly sexually transmitted disease service in a primary care clinic in Malaysia with a special focus on key populations. Challenges and key lessons learnt from its development and implementation are discussed. © Copyright 2018 American Sexually Transmitted Diseases Association All rights reserved.